Peningkatan kebermaknaan dan hasil belajar siswa melalui desain pembelajaran tematik terpadu alternatif berbasis projek pada siswa kelas 5 - Muti’atus Sa’adah; Mawardi Mawardi (Jurnal Riset Teknologi dan Inovasi Pendidikan (Jartika), 2019)
This research is motivated by the problem of thematic learning in SD Negeri Gendongan 02 which is less meaningful. It has an impact on low learning outcomes. Researchers choose an alternative integrated thematic learning design based on project to improve student meaningfulness and learning outcomes. This is classroom action research using the Stringer model. Research subjects involved 38 students. Data collection using questionnaires, written tests, documentation and observation sheets. Data analysis techniques uses descriptive comparative. The results showed that the meaningful learning in 1st cycle and 2nd cycle are 92.11% and 97.73%. Indonesian language learning outcomes in 1st cycle is 84.21% increasing to 86.84%. Learning outcomes of science studies in 1st and 2nd cycle are 65.79% and 84.21%. Based on the results of these research, the researsh is succesfull.